PENGOBATAN BELIAN PADA SUKU PETALANGAN DESA BETUNG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Erman "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated by the implementation of the tribe Petalangan treatment Belian Village Betung Pelalawan District of Pangkalan Kuras. The problems that arise from this study is how the implementation of the treatment Belian Village Petalangan and how the public perception on this Belian treatment. The purpose of this study was to determine how the implementation of Belian treatment and public perception of the treatment ritual Belian on Petalangan tribe. Location of the study was conducted in the village of Betung Pelalawan District of Pangkalan Kuras. The method used in this study using a qualitative descriptive study. As informants are community as much as 5 (five) while the data collection techniques using observation, interview by giving the question sheet. In analyzing the data from this study used a qualitative descriptive analysis method, while the validity of the data using triangulation techniques. The research found the implementation of medication purchases made by kemantan and pebayu and ketobung bat or drum to accompany spells read when performing the treatment, for the public perception of treatment may be as long as it does not violate the norms, ethics and religion.Keywords: Implementation, Belian Treatment, Tribe Petalangan, public perception